The Jordanian experience in distance education within the basic stage in light of the spread of the Coronavirus (COVID-19) - Alyousef, Raniah Ebrahem (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to know the effectiveness of the Jordanian experience in distance education within the basic stage in light of the spread of the Coronavirus (Covid-19) and to identify the challenges faced by governments to overcome this crisis and ensure the continuity of distance education, and the study was applied in the second semester 2020, and the study variables were studied. The independent, which was represented by distance education, gender male/female, basic stage, the Corona pandemic, and the dependent variable represented by the Coronavirus, the experience of e-learning on teaching and learning, and the experience of teachers in teaching.In light of the results, the researcher made the following recommendations:Providing adequate support to the Ministry of Education to maintain its continuity and capabilities to manage distance education.- Supporting national projects that develop distance education, and enhance cooperation between them and the Jordanian Ministry of Education.Continuously developing the distance education system, keeping pace with modern technological developments, and benefiting from the experiences of Arab countries.- Reconsidering the form of televised lessons and adding content that is attractive to students, especially stage students.
Keywords: E-learning; Coronavirus; the basic stage; learning